Betrayed : a Rosato & Associates novel - Scottoline, Lisa (Scottoline, Lisa. Rosato & DiNunzio novel., 2014)
"The women of Rosato & Associates return, after the relaunch of the series that started with Accused. This second entry, Betrayed, stars Judy Carrier, who has had the starring role in only one previous Rosato book. When Betrayed opens, Judy Carrier finds herself at a crossroads in her life. Her best friend, Mary DiNunzio, has just become partner and is about to become a bride, leaving Judy vaguely out of sorts. She's not jealous, but she's not happy either and she's wondering where her own career and love life are going. To make matters worse, she is rocked to her emotional foundations when she learns that her beloved Aunt Vicky has been diagnosed with breast cancer. She races to her aunt's side, and so does Judy's mother, only to find that her aunt is dealing with the sudden death of a friend who had been helping her through chemo. The friend, Emelia Juarez, was an undocumented worker at a local farm, but her death doesn't look natural at all, to Judy. Judy begins to investigate, following a path that leads her into an underground world far more dangerous than she ever imagined. Judy has to dig to uncover what happened to Emelia, and at the same time unearth the secrets in her own family"--